Sosialisasi Peningkatan Kesadaran Kesehatan Gigi pada Siswa SMA IT Al-Uswah Surabaya oleh B-Fresh Dental di BBPMP Surabaya - Yudy Prasetyo; Eni Nurhayati; Feri Lusianto; Nufikha Shafa Nabilla; Karista Dewi Pasa; Cherya Nurfajrin (STKIP PGRI Sidoarjo, 2024)
This community service was carried out to educate students and all parents that dental health is very important. Through this socialization, it is hoped that everyone is aware that dental health or dental care needs to be done. In particular, this socialization aims to provide insight and understanding to students and parents about dental health. This community service was carried out at SMA Al-Uswah Surabaya, with student participants and also competition participants. The obtaining Data using qualitative questionnaire. The results of this community service are that many of the students of IT Al-Uswah Surabaya High School have a very significant impact on awareness of maintaining dental health and they hope that this socialization event will become a routine agenda every year.